2014
DOI: 10.1080/13670050.2013.866624
|View full text |Cite
|
Sign up to set email alerts
|

Immersion education in the early years: a special issue

Abstract: Early years' immersion education programmes can be either monolingual or bilingual, and their objectives can range from language maintenance and/or enrichment to early second language learning, depending on the context of implementation. Here we examine some of the key issues and policy concerns relating to immersion education in the early years. Among these are difficulties associated with the term itself in certain political contexts, due to historical negative experience. Another issue discussed concerns th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 26 publications
(19 reference statements)
0
16
0
1
Order By: Relevance
“…• cooperative learning strategies" (May, Hill &Tiakwai 2004, p. 125) A number of researchers highlight importance of specific pedagogy and competence in the target language. Hickey and de Mejía (2013) argue that in-service provision is also necessary to retain experienced staff, stating There is a need for "high-quality and systematic ongoing training delivered by effective and experienced practitioners, allowing them to share their expertise. Such training needs to be accompanied by the development of adequate career structures where these are currently lacking, to promote better retention of the most effective and experienced practitioners" (Hickey and de Meja 2013, p.139).…”
Section: Irish-medium Professional Developmentmentioning
confidence: 99%
“…• cooperative learning strategies" (May, Hill &Tiakwai 2004, p. 125) A number of researchers highlight importance of specific pedagogy and competence in the target language. Hickey and de Mejía (2013) argue that in-service provision is also necessary to retain experienced staff, stating There is a need for "high-quality and systematic ongoing training delivered by effective and experienced practitioners, allowing them to share their expertise. Such training needs to be accompanied by the development of adequate career structures where these are currently lacking, to promote better retention of the most effective and experienced practitioners" (Hickey and de Meja 2013, p.139).…”
Section: Irish-medium Professional Developmentmentioning
confidence: 99%
“…However, Wong Fillmore (1985) established that success -in terms of the extent to which young children who are encountering the language used as the medium of instruction as an Hickey and De Mejía (2014), summarising a series of reviews of immersion education, note a consensus around the need for "language-rich instruction […] embedded in meaningful tasks" (p. 133) in the early years.…”
Section: Gaelic and Gaelic-medium (Gm) Preschool Provisionmentioning
confidence: 99%
“…As Hickey and De Mejía (2014) note, "Increasing recognition of the need for appropriate curricula for early years' education also presents early immersion with a challenge, if policy makers require the immersion preschool to do everything expected of mother-tongue preschools, and in the same way, but with the target language pasted on top" (p. 139). Notwithstanding the enhanced development of some cognitive functions such as some aspects of executive control and metalinguistic awareness which follow from growing up in a dual language environment (Barac, Bialystok, Castro & Sanchez, 2014), our study of children's experiences in GM preschool settings raised questions about the appropriateness of expectations about curriculum coverage, the training of practitioners, the nature of the language environment in the playroom and aspects of the learning environment that can be expected to enhance young children's learning, as well as issues of practitioner education in immersion pedagogies.…”
mentioning
confidence: 99%
“…The most common approach to immersion learning begins with total or near total immersion in the target language, wherein the target language is implemented from the moment students arrive in Kindergarten or first grade. Even though the children do not yet speak the language, research has shown that with enough input these students start to produce some output and begin to comprehend what they are being asked (Hickey & de Meija, 2014). Language immersion models generally include support in the development of academic literacy in two languages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the U.S., we have a large Spanish speaking population as well as numerous other minority language populations. Where the United States differs from other countries of the world is that second language learning is often not mandatory and in some instances is not even encouraged, creating a disparity between the United States and other developed countries (Hickey & de Meija, 2014).…”
Section: Introductionmentioning
confidence: 99%